IMPACT OF SEASONAL TOURISM ON REGIONAL ECONOMIES: A CASE STUDY OF HIMALAYAN DESTINATIONS - Devangana Verma; Arjun K (IJRDO- Journal of Educational Research, 2025)
This dissertation investigates the impact of seasonal tourism on the economic stability and growth of Himalayan destinations, addressing the critical issue of fluctuating tourist demand and its implications for local businesses and employment. Through a comprehensive analysis of tourist arrivals, seasonality patterns, local economic indicators, and community demographics, the study reveals that seasonal fluctuations in tourism significantly affect not only the economic viability of local enterprises but also the broader employment landscape. Key findings indicate that businesses experiencing high seasonal variability struggle with inconsistent revenue streams, often resulting in underemployment during off-peak seasons, which adversely affects community welfare and access to essential services, including healthcare. Furthermore, the study highlights that the economic challenges posed by seasonal tourism extend to healthcare systems, wherein inadequate financing and facility utilization during low tourism seasons compromise health service availability. The implications of these findings suggest a pressing need for targeted policy interventions that promote year-round tourism and diversify local economies, ultimately fostering community resilience and enhancing healthcare accessibility in these regions. This research contributes to the understanding of the intricate relationship between tourism dynamics and economic health, providing valuable insights for policymakers, stakeholders, and researchers focused on sustainable tourism and economic development in vulnerable areas.